Detoxification of Heavy Metal Ion-Contaminated Drinking Water by Green Technology - A Short Overview - Majumdar, Dipanwita (Current Green Chemistry, 2017)
Background: Certain heavy metals, in trace or ultra-trace quantities, are nutritionally essential as well as beneficial for a healthy life. This includes Cu, Zn, Fe, Ni, Cr, etc. which in fact although required by the living body in minute quantities but become toxic in larger dosages. Besides, heavy metals such as Pb, Hg, As, Cd are most often responsible to human poisoning. Method: Most of them accumulate and travel up the food chain when discharged into surface water bodies from industrial, agricultural as well as domestic effluents due to man-made activities. In certain cases, they are also contaminated through natural causes such as soil/rock erosion, and salination too. These heavy metals through various means percolate into groundwater, thereby contaminating drinking water - which of-course, is a very important global issue to be concerned about. Result: To accomplish distribution of clean and fresh drinking water and promote wastewater management, varieties of green chemistry based- techniques as well as methodologies for heavy metal ion remediation are being employed today. Conclusion: This review aims at highlighting the commonly existing green- technologies adopted for remediation of heavy metals to obtain purified water.
Keywords: heavy metal ion